2018
DOI: 10.3390/polym10050474
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light and Solar Light Activated Self-Healing Epoxy Coating having Enhanced Properties Using MXene Flakes as Multifunctional Fillers

Abstract: Two issues are required to be solved to bring intrinsically self-healing polymer coatings into real applications: remote activation and satisfied practical properties. Here, we used MXene, a newly reported two-dimensional material, to provide an epoxy coating with light-induced self-healing capabilities and we worked to enhance the properties of that coating. The self-healing coatings had a reversible crosslinking network based on the Diels-Alder reaction among maleimide groups from bis(4-maleimidopheny)methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…MXenes is a family of 2D transition metal carbides, carbonitrides, and nitrides. Due to their outstanding mechanical, thermal, and electrical properties, these multilayered compounds have been employed to realize multifunctional epoxy-based nanocomposites characterized by enhanced electrical and thermal conductivity, self-healing characteristics, excellent toughness, and mechanical properties, even at low filler percentages (1 wt.%) [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Nanofillers For Epoxy Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…MXenes is a family of 2D transition metal carbides, carbonitrides, and nitrides. Due to their outstanding mechanical, thermal, and electrical properties, these multilayered compounds have been employed to realize multifunctional epoxy-based nanocomposites characterized by enhanced electrical and thermal conductivity, self-healing characteristics, excellent toughness, and mechanical properties, even at low filler percentages (1 wt.%) [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Nanofillers For Epoxy Resinsmentioning
confidence: 99%
“…MXenes is a family of 2D transition metal carbides, carbonitrides, and nitrides. Due to their outstanding mechanical, thermal, and electrical properties, these multilayered compounds have been employed to realize multifunctional epoxy-based nanocomposites characterized by enhanced electrical and thermal conductivity, self-healing characteristics, excellent toughness, and mechanical properties, even at low filler percentages (1 wt.%) [46][47][48][49][50]. The positive effects of the nano-Al2O3, especially on mechanical properties (the nanoparticles are able to significantly increase the strength at the fiber/matrix interface [52]), can be found also when these particles are added in fiber reinforced composites based on an epoxy matrix, even at very low contents (i.e., 1-0.5 wt.%) [53][54][55].…”
Section: Carbon-based Nanofillersmentioning
confidence: 99%
“…This relatively new class of ionic nanocomposites combines filler reinforcement with the reversibility of ionic interactions [23]. Despite the improved mechanical performance, the reversible feature of ionic bonds, that can break and reform under certain conditions [21], has led to smart materials for self-healing [25,26], shape-memory [21,22], piezoelectric [27], and mechanochromic [28] applications due to their ability to respond directly under a certain chemical or physical stimulus. For instance, nanocomposites based on imidazolium-functionalized polyurethane and surface-modified sulfonate silica (SiO 2 ) NPs have revealed not only unprecedented mechanical properties with simultaneous improvements in stiffness, toughness and extensibility but also a scratch recovery ability [21].…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al added MXenes flakes into epoxy and reported the enhanced nearinfrared light and solar light-activated self-healing behavior of epoxy in the presence of MXenes fillers. [33] In a work by Chen et al, they reported the improvement in electrical, dielectric, and thermal properties of an epoxy composite containing MXenes platelets. [34] Feng et al added 1.2 wt% of MXenes into the commercial epoxy system and reported good electrical conductivity (4.52 × 10 −6 S cm −1 ) and moderate tensile strength (66.2 MPa).…”
Section: Introductionmentioning
confidence: 99%